Projeto show de física da UNESP de Rio Claro: resultados de 2013 a 2015 - Ferrazo, André Kyoshi Fujii [UNESP]; Gozzi, Giovani [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Project " Show de Física " offers to the basic education schools of Rio Claro and other cities of the region demonstrations and physical experiments about various subjects about physics, such as mechanics, optics , electricity, magnetism, pressure and low temperatures . This project is part of the regular activities of the Department of Physics, IGCE, since 2002 and has the visitation capacity of about 1800 students visitors per year. The main objective is to provide to the basic education students the opportunity deal with physical experiments and demonstrations, which has sound and visuals striking. A computerized audio-visual control system it is used to become the show even more dynamic and attractive. The audio-visual control system it is used to enable the exploitation of images and videos to establish the relationship between the physical concepts with everyday situations, stimulating the visitors curiosity by the different concepts of physics. The web-page of Show da Física in a social network, created in April 2013, allows to students (visitors) the possibility to access photographic material, to do comments and to do the Show da Física part of your profile on the network. On this page, the students establishes good contact with the scientific, cultural and technological development issues, because the page share posts, curiosities and innovations about the development of science. On the other hand, it is performed continuous efforts in the in physics undergraduate students education and training. In the past three years, twelve undergraduate students acted as the show staff and monitoring of the presentations as well. The staffs undergraduate students developed a series of activities, including the production of audio-visual material to physics teaching, the theoretical deepening of the topics discussed during the show, the development of new experimental approaches. Al this developed materials were produced considering the visitors cognitive phase, once the physics show visitors are students from elementary school and also high school. During the every year, the show staffs develop scientific work and show it in undergraduate research conferences and in university extension conference. In the last three years seven works were presented in the Scientific Initiation Congress of UNESP. In the same period were performed two scientific divulgation activities external to the UNESP: the participation in the week of science and technology, where there were performed demonstrations for a large number of audience in the Rio Claro Shopping Centre and four other performances at 67o. Encontro da Sociedade Brasileira para o Progresso da Ciência (SBPCJovem), which took place in the São Carlos City on 15 and 16 July. In summary, the Sho de Física (Physics Show) has contributed to the democratization of scientific knowledge, specifically about Physics, by two ways: providing an auxiliary tool for the basic level education and educating (training) undergraduate students of the Department of Physics IGCE as well. As proposal of future activities it is expected to provide a physics teaching material to the basic level teachers that visits the project Show de Física. This paper presents the results of the project Show de Física obtained in the last three years 2013-2015.

O projeto de extensão universitária “Show de Física” disponibiliza para as escolas do ensino básico de Rio Claro e região, vivências, demonstrações e experimentos de física sobre diversos assuntos, como mecânica, óptica, eletricidade, magnetismo, pressão e baixas temperaturas. Este projeto faz parte das atividades regulares do Departamento de Física do IGCE desde 2002 e tem capacidade de receber a visitação de cerca de 1.800 estudantes por ano. O principal objetivo é proporcionar aos estudantes do ensino básico a possibilidade de interagir com experimentos e demonstrações de física. Estas atividades utilizam recursos sonoros e visuais impactantes, contando com um sistema computadorizado de controle de recursos áudiosvisuais, o que torna o show ainda mais dinâmico e, atrativo, possibilitando a exploração de imagens e vídeos para estabelecer relação entre os assuntos abordados com situações do cotidiano. Com estes recursos busca-se aguçar a curiosidade dos estudantes pelos diversos conceitos da física. A página do Show de Física em uma rede social criada em abril de 2013 permite que os estudantes visitantes possam acessar material fotográfico, fazer comentários e tornar o Show de Física parte de seu perfil na rede. Nessa página os estudantes ainda têm a chance estabelecer maior contado com o desenvolvimento científico, cultural e tecnológico, devido a postagem de artigos, curiosidades e novidades no desenvolvimento da ciência. Por outro lado, o projeto tem sido constante na formação dos graduandos em física do IGCE. Nos últimos três anos, doze graduandos atuaram como monitores do show. Além da monitoração das apresentações, os graduandos participantes desenvolvem uma série de atividades, entre elas a produção de material audiovisual voltado para o ensino de física, o aprofundamento teórico nos assuntos abordados durante o show e a construção de novas abordagens para os experimentos. Estes materiais são desenvolvidos pelos monitores sempre respeitando a fase cognitiva em que se encontram os visitantes, já que o show conta com a participação de estudantes do ensino fundamental e ensino médio. Durante o ano os monitore tem como atividade o desenvolvimento de trabalhos que resultam na participação em congressos de iniciação científica e congresso de extensão universitária, o que levou a apresentação de sete trabalhos nos últimos três anos no Congresso de Iniciação Cientifica da UNESP. Ainda nos últimos três anos ocorreram duas atividades externas à UNESP com foco na divulgação científica: a participação na semana de ciência e tecnologia, onde ocorreram demonstrações para um grande número pessoas no Shopping Center de Rio Claro; e quatro apresentações no 67º. Encontro da Sociedade Brasileira para o Progresso da Ciência (SBPC-Jovem), que ocorreu nos dias 15 e 16 de Julho de 2015, em São Carlos, São Paulo. Desta forma, o Show de Física tem contribuído para a democratização do conhecimento científico, especificamente na área de física, de duas maneiras: disponibilizando um instrumento auxiliar para o ensino a nível básico e também auxiliando na formação de graduandos dentro do Departamento de Física do IGCE. Como proposta para trabalhos futuros espera-se a disponibilização de material de apoio didático aos professores da rede básica de ensino de Rio Claro e região, os quais visitam o projeto Show de Física. O presente trabalho apresenta detalhadamente os resultados do projeto Show de Física que foram alcançados no período de 2013 a 2015.
Keywords: Show de física; Physics teaching; Education; Show de física; Ensino de física